Portraits d'Artistes - Thorn-Petit, Liliane (Luxembourg : RTL Edition, 1987)
Adami, Valerio ; Arman ; Bertemes, Roger ; Bissière, Louttre ; Bissière, Roger ; Botero, Fernando ; Brasilier, André ; Brocquy, Louis Le ; Camacho, Candido ; Cavallo, Ricardo ; Christo ; Reinhoud ; Debré, Olivier ; Delahaut, Jo ; Dodeigne, Eugène ; Fassianos, Alekos ; Friedlaender, Gotthard ; Guttuso, Renato ; Hajdu, Etienne ; Henein, Adam ; Jenkins, Paul ; Karskaya, Ida ; Klein, Yves ; Les Lalanne ; Landuyt, Octave ; Van Lint, Louis ; López Garcia, Antonio ; Oppenheim, Meret ; Pan, Marta ; Pistoletto, Michelangelo ; Pomodoro, Gio ; Poncet, Antoine ; Probst, Joseph ; Rainer, Arnulf ; Reuterswärd, Carl Fredrik ; de Saint-Phalle, Niki ; Saura, Antonio ; Schneider, Gérard ; Segard, Aljocha ; Soto, Jesus Rafael ; Thalmann, Gérard ; Tinguely, Jean ; Titus-Carmel, Gérard ; Tongiani, Vito ; Wercollier, Lucien
Interviews met kunstenaars uitgezonden op RTL vanaf 1983-04-22
Frans
boek